Getting to the rule of law - Fleming, James E. (Nomos, 2011)
"The rule of law has been celebrated as 'an unqualified human good, ' yet there is considerable disagreement about what the ideal of the rule of law requires. When people clamor for the preservation or extension of the rule of law, are they advocating a substantive conception of the rule of law respecting private property and promoting liberty, a formal conception emphasizing an 'inner morality of law, ' or a procedural conception stressing the right to be heard by an impartial tribunal and to make arguments about what the law is? When are exertions of executive power 'outside the law' justified on the ground that they may be necessary to maintain or restore the conditions for the rule of law in emergency circumstances, such as defending against terrorist attacks? In Getting to the Rule of Law a group of contributors from a variety of disciplines address many of the theoretical legal, political, and moral issues raised by such questions and examine practical applications 'on the ground' in the United States and around the world. This timely, interdisciplinary volume examines the ideal of the rule of law, questions when, if ever, executive power 'outside the law' is justified to maintain or restore the rule of law, and explores the prospects for and perils of building the rule of law after military interventions."--Publisher's description